Ultra High Temperature Treatment, but Not Pasteurization, Affects the Postprandial Kinetics of Milk Proteins in Humans - Lacroix, Magali; Bon, Cyriaque; Bos, Cécile; Léonil, Joëlle; Benamouzig, Robert; Luengo, Catherine; Fauquant, Jacques; Tomé, Daniel; Gaudichon, Claire (The Journal of nutrition, 2008)
Although the chemical and physical modifications to milk proteins induced by technological treatments have been characterized extensively, their nutritional consequences have rarely been assessed in humans. We measured the effect of 2 technological treatments on the postprandial utilization of milk nitrogen (N), pasteurization (PAST) and ultra high temperature (UHT), compared with microfiltration (MF), using a sensitive method based on the use of milk proteins intrinsically labeled with ¹⁵N. Twenty-five subjects were studied after a 1-wk standardization of their diet. On the day of the investigation, they ingested a single test meal corresponding to 500 mL of either MF, PAST, or UHT defatted milk. Serum amino acid (AA) levels as well as the transfer of ¹⁵N into serum protein and AA, body urea, and urinary urea were determined throughout the 8-h postprandial period. The kinetics of dietary N transfer to serum AA, proteins, and urea did not differ between the MF and PAST groups. The transfer of dietary N to serum AA and protein and to body urea was significantly higher in UHT than in either the PAST or MF group. Postprandial deamination losses from dietary AA represented 25.9 ± 3.3% of ingested N in the UHT group, 18.5 ± 3.0% in the MF group, and 18.6 ± 3.7% in the PAST group (P < 0.0001). The higher anabolic use of dietary N in plasma proteins after UHT ingestion strongly suggests that these differences are due to modifications to digestive kinetics and the further metabolism of dietary proteins subsequent to this particular treatment of milk.